POLITIK ETIKA DALAM PERUBAHAN â€œMALE â€“ FEMALE STYLEâ€ - Zaelany, Andy Ahmad (Jurnal Psikologi, 2006)
The topic of â€œMale-Female Styleâ€ is related to the body language (in German: koerper-Sprache), which is in practice become a cover of person identity. Each sexhas socio-culturally a certain area of body language. Community who is supporter of a culturerequires the existence of harmonization between body language with its sex in daily activities.Attitudes and behaviors which create a disharmony of body language and its sex will arousedenunciation and negative acceptance from community toward certain individual.The socio-cultural implication of the change of â€˜male-female styleâ€™ is vast, especially onthe aspects of demography and culture. The mistakes in the anticipation and the management ofchange could cause a social unrest.